The Shared Tenancy in Peru: analysis of its effects on the Principle of Best Interest of the Child and Adolescent - Ampuero Barrantes, Dora Carmela (2024)
The article examines the recent regulation of shared possession in Peru and its impact on the Principle of the Best Interest of the Child and Adolescent. Other studies carried out from comparative law are taken into account. The advantages and disadvantages of this regulation in the development of the minor are analyzed, considering the changes introduced by the new legislation. The comparative legal method is used based on a review of the bibliography from a documentary analysis in which judicial files related to shared ownership in Peru are reviewed. The influence of regulatory changes in guaranteeing the best interests of the minor is assessed. Criteria that determine the effectiveness and possible impacts of shared ownership on the families that adopt it are evaluated.